الأراضي المفتوحة صلحاً في عصر الرسول والخلفاء الراشدین - د .مرتضى جلیل جعیلان د . مھند عبد الرضا حمدان (College of Education for Women, 2019)
Islam has paid great deal of attention to land issue where has been considered most resources for providing Muslims with water and food and building on that we notice that the Islamic government worked hardly to give attention ton the land especially newly included under control of Muslims especially that they had got with out fighting or bloodshed but had been included via reconciliation with the landlords so the Muslims had share in that would be taken either in cash or in materials in a value would be differentiated following several issues like type of harvest and method of watering the land and religion of the landlords. So Muslims had listed laws and rules that enable them typical investment for that lands , Due to importance of the topic we had taken that in research Chronological history taking in mine the policies of that different Islamic governments towards that lands that had been gained in reconciliation by Muslims with caring that these political disagreements meant with caring to high interests of Islamic state and to keep the Arabs as warrior nation without caring to agriculture, But to keep landlords on their lands , as well as maintaining stable financial source for Islamic state and to preserves on interests of next generations in that lands without keeping that lands under custody of a certain Muslims category , Also the Islamic government was careful that he who would undertake farming land is the most acknowledged in farming it and most capable rather than others , This proves that Muslims were careful to adopt correct policies towards agricultural lands and it's big importance in public life of Muslims.